A STUDY OF DIFFERENTIAL ITEM FUNCTIONING IN A SOCIAL SKILLS SCALE FOR ADOLESCENTS - Hidalgo Montesinos, María Dolores; Galindo Garre, Francisca; Inglés Saura, Cándido José; Campoy Menéndez, Guillermo; Ortiz Soria, Beatriz (Anales de Psicología / Annals of Psychology, 1999)
The purpose of this study was to determine the differential item functioning (DIF) of the Interpersonal Difficulty Scale for Adolescents (EHSPA) as part of the item analysis process. This study used two different DIF detection procedures (Mantel-Haenszel statistic and Logit Models) to evaluate the extent to which items in ESHPA functioned differently for matched gender groups.